Computational fluid dynamic analysis of a simplified rectangular profile scroll case design for micro hydro propeller turbine - Marfori, Isidro Antonio V., III (Animo Repository, 2007)
The aim of this study is to determine the characteristic of a rectangular profile scroll case design in a small hydro propeller turbine using computational fluid dynamics (CFD) software in order to optimize and produce a design with desirable features. Related studies concluded that for a small capacity hydro system, the turbine design must be simple and robust which in sure makes the turbine inefficient. However, even a simple turbine design can still be efficient through optimization.